Incidence of Cavum Septum Pellucidum and Cavum Vergae in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia - Faried, Ahmad; Soeprajogo, Adolf Setiabudi; Melia, Regina; Arifin, Muhammad Zafrullah (International Journal of Integrated Health Sciences, 2017)
Objective: To describe the cavum septum pellucidum (CSP) and cavum vergae (CV) findings. Methods: Thirteen samples were recruited in the study. The study was conducted at the Department of Neurosurgery, Dr. Hasan Sadikin Hospital, Bandung, Indonesia in the period of 2015–2016. Thirteen samples were recruited for the study. Cavum septum pellucidum and CV spaces are relatively rare. During neurology and neurosurgery examination of patients with head computed tomography (CT) scan and magnetic resonance imaging (MRI), CSP and CV were discovered accidentally. The incidence of these unique spaces reported from many countries, but have never been reported from Indonesia.Results: This is the first-time reported incidental finding of CSP and CV from Indonesia, 13 cases in one-year period. Since the presence of CSP and CV is usually asymptomatic, clinician seem don’t really care to put it in their report.Conclusions: The presence of CSP and CV as a common incidental finding can be more revealed in our country in years to come and hopefully can be more studied in term of anatomical landmark on neurosurgical field.Keywords: Cavum septum pellucidum, cavum vergae, incidental finding DOI: 10.15850/ijihs.v5n1.964